Comparison of the effects of modified constraint-induced movement therapy and intensive conventional therapy with a botulinum-a toxin injection on upper limb motor function recovery in patients with stroke. Issue 1 (1st January 2019) - Nasb, Mohammad; Li, Zhenlan; S.A. Youssef, Ahmed; Dayoub, Lamis; Chen, Hong
ABSTRACT: Stroke is the second leading cause of mortality worldwide and one of the main causes of adult disability. Many studies have suggested that combination therapies provide better outcomes in patients with stroke than monotherapies. The combination of botulinum-A toxin (BTX) injection with rehabilitation methods, such as modified constraint-induced movement therapy (BTX-mCIMT), has emerged as a highly promising intervention for promoting motor recovery after stroke. Thus, the present study compared the effectiveness of the combination of BTX with high-dose conventional therapy (BTX-ICT) and BTX-mCIMT for improving motor recovery and reducing spasticity of the upper limb in patients with stroke. This study recruited 64 patients with stroke. The patients were randomly allocated to two groups, namely, BTX-ICT and BTX-mCIMT. Modified Ashworth scale (MAS), Fugl–Meyer assessment (FMA), and Barthel index (BI) assessment scores were determined for the patients in both the groups before and at 4 weeks after the BTX injection. After four weeks of treatment, the MAS, FMA, and BI assessment scores of the patients in both groups were significantly higher than the scores before the treatments (P < 0.05). At the end of 4 weeks, the patients in the BTX-mCIMT group showed significantly higher mean FMA and BI assessment scores than the patients in the BTX-ICT group (P < 0.05). However, no significant statistical difference was observed in the MAS score of the patients in the two groups (P > 0.05). Our results indicated that while both BTX-mCIMT and BTX-ICT promoted motor function recovery in patients with stroke, BTX-mCIMT exerted higher therapeutic effects than BTX-ICT on motor function recovery and in the activities of daily living of patients with stroke.